Effects of modified Soyo-san (Xiao-yao-san, Shoyo-san) combined with antidepressants on post-stroke depression and functional recovery: a systematic review and meta-analysis - Bak, Jeongrim; Jin, Hyowon; Yun, Jong-Min; Leem, Jungtae (Frontiers in Pharmacology, 2026)
BackgroundOver one-third of stroke survivors experience Post Stroke Depression. Conventional antidepressants are effective but have adverse effects. Soyo-san is an herbal medicine used to treat neuropsychiatric diseases that may exert antidepressant effects with fewer adverse effects. However, there is insufficient evidence synthesizing existing Randomized Controlled Trials to provide comprehensive guidance on the effectiveness and safety of combination treatment with Soyo-san.PurposeWe evaluated the additional benefits and safety of combining Soyo-san with conventional antidepressants for treating Post Stroke Depression through a systematic review and meta-analysis.MethodsA comprehensive search of seven databases was conducted on October 10, 2024, followed by study selection and data extraction. Methodological quality was assessed using the Cochrane Collaboration’s risk-of-bias tool, and evidence quality was evaluated using the Grading of Recommendations Assessment, Development, and Evaluation method. Quantitative data synthesis and meta-analysis were conducted using RStudio, along with subgroup, sensitivity, and publication bias analyses.ResultsThe search retrieved 41 RCTs with 3,628 participants. Soyo-san had a significant effect on depression based on Hamilton Depression Scale score (MD: −4.01; 95% CI: −4.72, −3.30; I2 = 94%) and total effective rate (RR: 1.21; 95% CI: 1.17, 1.25; I2 = 0%) with any antidepressant. Moreover, Soyo-san improved post-stroke recovery of motor, cognitive, and sleep dysfunctions. Adverse events were reported in both treatment and control groups in most studies but were less frequent in the former.ConclusionModified Soyo-san combined with antidepressants was associated with improvements in depressive symptoms and variety of functional outcomes, though the certainty of evidence is low to very low. Therefore, these findings should be interpreted with caution, and high-quality international trials are needed before firm conclusions can be drawn.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024510361, identifier CRD42024510361.